Portfolio assessment with dimension of learning: an approach on the mastery of concept - Nurkhairo Hidayati; Tengku Idris; Peny Husna Handayani; Fitri Arsih (JURNAL BIOEDUKATIKA, 2021)
Portfolio assessment with the dimension of learning approach is an ideal combination to improve mastery concept and habits of mind students. The use of this assessment and approach can fully describe the students abilities during the learnig process. This study aims to determine the effect of using portfolio assessment with the dimension of learning approach on students' mastery of concepts on the excretion system material at the state senior high school in Pekanbaru City. This research is a weak experiment research with pretest posttest group design. The instrument in this study was a matter of conceptual mastery using Marzanos taxonomy. The instrument used was valid and reliable with a value of 0.56. The data were processed descriptively using the N-Gain formula and inferential statistics with one sample t test with a value of 0.31. The results of this study indicate that the students' mastery of concepts after the use of portfolio assessment with the dimension of learning approach increased for W senior high school 0.39 (sufficient); X senior high school 0.54 (sufficient); Y senior high school 0.68 (sufficient) and  Z senior high school0.39 (sufficient) with an average of 0.50 in the sufficient category. After the inferential test was carried out, it was obtained tcount (10.67)> ttable (0.00) so that it could be concluded that the use of portfolio assessment with the dimension of learning approach could significantly influence students' mastery of concepts. Referring to the findings of this study, teachers at the senior high school level, especially in the field of biology, can use portfolio assessment with the dimension of learning approach as a form of innovative assessment in the learning process.